2013
DOI: 10.1007/s00231-013-1163-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhance of heat transfer on unsteady Hiemenz flow of nanofluid over a porous wedge with heat source/sink due to solar energy radiation with variable stream condition

Abstract: Nanofluid-based direct solar receivers, where strongly absorb aQ4 selectiVely absorb incident radiation. nanoparticles in a liquid medium caa scatter and absorb solar Based on the pdiation and Brownian motion properties of radiation, have recently received interest to efficiently distribnanoparticle, the utilization of nanofluids in solar thermal ute and store the thermal energy. The objective of the present system becomes the new study hotspot. work is to investigate theoretically the unsteady homogeneous Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Mohamad et al [62] analyzed the influence of the copper nanoparticles in the presence of magnetic field on unsteady Hiemenz flow and heat transfer of incompressible Cunanofluid along a porous wedge sheet due to solar energy. The conclusion was drawn that the temperature is significantly influenced by magnetic strength, nanoparticle volume fraction, convective radiation and porosity of the wedge sheet.…”
Section: Heat and Nanofluid Transfermentioning
confidence: 99%
“…Mohamad et al [62] analyzed the influence of the copper nanoparticles in the presence of magnetic field on unsteady Hiemenz flow and heat transfer of incompressible Cunanofluid along a porous wedge sheet due to solar energy. The conclusion was drawn that the temperature is significantly influenced by magnetic strength, nanoparticle volume fraction, convective radiation and porosity of the wedge sheet.…”
Section: Heat and Nanofluid Transfermentioning
confidence: 99%
“…Homotopy solutions for Blasius flow of second grade fluid in the presence of thermal radiation effects have been derived by Hayat et al (2009). Some recent studies pertaining to linear radiation heat transfer can be found in Bhattacharyya (2011), Nadeem and Haq (2012), Khan et al (2012), Motsumi and Makinde (2012), Hady et al (2012), Gireesha et al (2013), Mohamad et al (2013) and Antar et al (2014). Magyari (2010) indicated that linear radiation problem for flow past a flat plate can be simply reduced to re-scaling of Prandtl number by a factor involving radiation parameter.…”
Section: Introductionmentioning
confidence: 99%
“…(6) results in a highly nonlinear energy equation in and it is difficult to obtain its solution. However, researchers have solved this problem in past by assuming small temperature differences within the flow (see [39] [49] ). In this situation, Rosseland formula can be linearized about ambient temperature .…”
Section: Problem Formulationmentioning
confidence: 99%
“…Effect of incident radiation due to solar energy in an incompressible flow of nanofluid has been presented by Kandasamy et al [48]. Heat transfer enhancement in the unsteady Hiemenz flow of nanofluid past a wedge has been discussed by Mohamad et al [49]. The above mentioned studies were confined to the linear radiative heat transfer effects which are only valid for small temperature differences.…”
Section: Introductionmentioning
confidence: 99%